Response of large benthic foraminifera to climate and local changes: Implications for future carbonate production. Issue 1 (18th May 2021) - Narayan, Gita R.; Reymond, Claire E.; Stuhr, Marleen; Doo, Steve; Schmidt, Christiane; Mann, Thomas; Westphal, Hildegard
Abstract: Large benthic foraminifera are major carbonate components in tropical carbonate platforms, important carbonate producers, stratigraphic tools and powerful bioindicators (proxies) of environmental change. The application of large benthic foraminifera in tropical coral reef environments has gained considerable momentum in recent years. These modern ecological assessments are often carried out by micropalaeontologists or ecologists with expertise in the identification of foraminifera. However, large benthic foraminifera have been under‐represented in favour of macro reef‐builders, for example, corals and calcareous algae. Large benthic foraminifera contribute about 5% to modern reef‐scale carbonate sediment production. Their substantial size and abundance are reflected by their symbiotic association with the living algae inside their tests. When the foraminiferal holobiont (the combination between the large benthic foraminifera host and the microalgal photosymbiont) dies, the remaining calcareous test renourishes sediment supply, which maintains and stabilizes shorelines and low‐lying islands. Geological records reveal episodes (i.e. late Palaeocene and early Eocene epochs) of prolific carbonate production in warmer oceans than today, and in the absence of corals. This begs for deeper consideration of how large benthic foraminifera will respond under future climatic scenarios of higher atmospheric carbon dioxide ( p CO2 ) and to warmer oceans. In addition, studies highlighting the complex evolutionary associations between large benthic foraminifera hosts and their algal photosymbionts, as well as to associated habitats, suggest the potential for increased tolerance to a wide range of conditions. However, the full range of environments where large benthic foraminifera currently dwell is not well‐understood in terms of present and future carbonate production, and impact of stressors. The evidence for acclimatization, at least by a few species of well‐studied large benthic foraminifera, under intensifying climate change and within degrading reef ecosystems, is a prelude to future host–symbiont resilience under different climatic regimes and habitats than today. This review also highlights knowledge gaps in current understanding of large benthic foraminifera as prolific calcium carbonate producers across shallow carbonate shelf and slope environments under changing ocean conditions.